2019
DOI: 10.1002/mus.26616
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral nerve conduction studies in the evaluation of distal symmetric polyneuropathy

Abstract: Introduction Nerve conduction studies are used to aid in the diagnosis of distal symmetric polyneuropathy (DSP). It is unclear whether bilateral lower extremity nerve conduction studies (NCS) are needed when evaluating for suspected DSP. Methods We retrospectively analyzed NCS from patients who presented to the University of Michigan electromyography laboratory between July 1, 2016 and December 31, 2017 with symptoms of DSP to assess agreement and correlation between left and right lower extremity NCS paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…199,202,203 Studies of both legs may increase diagnostic certainty although symmetrical findings are very common (Cohen's kappa agreement between legs 0.5 and 0.9). 204 Initial studies of the sural to radial nerve amplitude ratio reported a sensitivity and specificity of 90% using the cutoff ratio of <0.4. However, more recent studies report poor sensitivity, equivalent to that of sural responses alone, and less sensitive than medial plantar responses in one cohort.…”
Section: Diabetic Neuropathymentioning
confidence: 99%
See 1 more Smart Citation
“…199,202,203 Studies of both legs may increase diagnostic certainty although symmetrical findings are very common (Cohen's kappa agreement between legs 0.5 and 0.9). 204 Initial studies of the sural to radial nerve amplitude ratio reported a sensitivity and specificity of 90% using the cutoff ratio of <0.4. However, more recent studies report poor sensitivity, equivalent to that of sural responses alone, and less sensitive than medial plantar responses in one cohort.…”
Section: Diabetic Neuropathymentioning
confidence: 99%
“…Prolonged F wave latencies have been proposed as highly sensitive marker of DSPN, although robust diagnostic studies are lacking 199,202,203 . Studies of both legs may increase diagnostic certainty although symmetrical findings are very common (Cohen's kappa agreement between legs 0.5 and 0.9) 204 . Initial studies of the sural to radial nerve amplitude ratio reported a sensitivity and specificity of 90% using the cutoff ratio of <0.4.…”
Section: Polyneuropathymentioning
confidence: 99%
“… 3 There are many screening and diagnostic methods for DPN, among which neuroelectrophysiological examination is objective, sensitive and reliable, and is often regarded as the gold standard. 4 , 5 Nerve conduction studies (NCS) are an essential tool in the evaluation of the peripheral nervous system. 6 It determines the functional status of peripheral nerves by examining the muscular nerve conduction function of the affected limb.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostic guidelines have been established to standardize diagnostic procedures and scientific reporting [ 5 ]. Algorithms include clinical and electrodiagnostic testing, serological markers, and skin and/or peripheral nerve biopsies [ 6 , 7 ]. Sural nerve biopsy is recommended to detect demyelination and axonal damage, and to differentiate inflammatory disorders (e.g.…”
Section: Introductionmentioning
confidence: 99%